2010
DOI: 10.1163/001121610x521190
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Habitat Fragmentation on the Amphidromous Freshwater Shrimp, Caridina Leucosticta (Decapoda, Atyidae) in a Rice Paddy Drainage Channel

Abstract: Agricultural channels can be important habitats for aquatic species inhabiting agricultural areas. However, water supply in agricultural channels can vary substantially with types of agriculture and irrigation/drainage system, and thereby affect the viability of local populations of aquatic species. In this study, we focused on the amphidromous freshwater atyid shrimp Caridina leucosticta. To clarify whether C. leucosticta utilizes agricultural channels as a habitat in relation to fluctuations in the water sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In September and October, C. leucosticta accounted for nearly half of the roughly three hundred specimens collected in H03, but they were seldom collected in H04 (Saito et al, unpublished data), suggesting that their upstream migration is blocked by some physical barrier between these two stations. Nakata et al (2010) reported that C. leucosticta occurs in high density in the middle reaches of Toyokawa River, Aichi Prefecture, central Japan, which is roughly 20 km upstream of the river mouth. This result suggests that C. leucosticta is capable of migrating much longer distance upstream than what has been observed in the present study, if the gradient is gradual and vegetation continuously cover river bank.…”
Section: Limiting Factors For Shrimp Distributionmentioning
confidence: 99%
“…In September and October, C. leucosticta accounted for nearly half of the roughly three hundred specimens collected in H03, but they were seldom collected in H04 (Saito et al, unpublished data), suggesting that their upstream migration is blocked by some physical barrier between these two stations. Nakata et al (2010) reported that C. leucosticta occurs in high density in the middle reaches of Toyokawa River, Aichi Prefecture, central Japan, which is roughly 20 km upstream of the river mouth. This result suggests that C. leucosticta is capable of migrating much longer distance upstream than what has been observed in the present study, if the gradient is gradual and vegetation continuously cover river bank.…”
Section: Limiting Factors For Shrimp Distributionmentioning
confidence: 99%